2021
DOI: 10.1177/17562872211032485
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of magnetic stimulation for female stress urinary incontinence: a meta-analysis

Abstract: Aim: This meta-analysis aimed to evaluate the efficacy of magnetic stimulation (MS) in treating female stress urinary incontinence (SUI) and providing an alternative treatment for patients who are unwilling to undergo surgery. Methods: Randomized controlled trials (RCTs) that evaluated MS as a remedy for female SUI were retrieved from various electronic databases, including MEDLINE, EMBASE, and the Cochrane Controlled Trial Registry system. Moreover, reference lists for related papers were carefully screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…39,40 Similarly, despite limitations to the data that include significant heterogeneity in the data and stimulation protocols, all meta-analyses comparing magnetic stimulation to sham or placebo concluded that magnetic stimulation appears to be safe and may be effective in reducing SUI. [41][42][43] A Cochrane review 44 of 3,781 patients in 51 studies comparing non-implanted electrical stimulation (ES) to various other interventions (PFME, vaginal cones, sham) or no intervention provided the most robust evidence on ES. While the review indicated that ES is more effective than sham or no active treatment, it was not possible to say whether or not ES has similar efficacy to PFME or other active treatments.…”
Section: Future Directions Educational Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Similarly, despite limitations to the data that include significant heterogeneity in the data and stimulation protocols, all meta-analyses comparing magnetic stimulation to sham or placebo concluded that magnetic stimulation appears to be safe and may be effective in reducing SUI. [41][42][43] A Cochrane review 44 of 3,781 patients in 51 studies comparing non-implanted electrical stimulation (ES) to various other interventions (PFME, vaginal cones, sham) or no intervention provided the most robust evidence on ES. While the review indicated that ES is more effective than sham or no active treatment, it was not possible to say whether or not ES has similar efficacy to PFME or other active treatments.…”
Section: Future Directions Educational Opportunitiesmentioning
confidence: 99%
“…39,40 Similarly, despite limitations to the data that include significant heterogeneity in the data and stimulation protocols, all meta-analyses comparing magnetic stimulation to sham or placebo concluded that magnetic stimulation appears to be safe and may be effective in reducing SUI. 41-43…”
Section: Future Directionsmentioning
confidence: 99%
“…MS is a non-invasive therapeutic device that interacts with the neuromuscular tissue through a specific electromagnetic field, inducing intense contractions (involuntary and otherwise unachievable regular gym training or superficial electrical stimulation) that stimulate pelvic floor muscles deep down and restoring neuromuscular control. Various clinical trials have evaluated the efficacy of MS in ameliorating female SUI with positive outcomes [ 27 ]. However, due to heterogeneous results and weak evidence of the short-term and long-term effects, current European Urology Association recommendations advise against treating urinary with magnetic stimulation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fitz et al [20] and Felicíssimo et al [21] reported equal benefits of supervised (outpatient) and unsupervised (home programs) PFMT for improving female SUI, and this may be considered an option for self-management strategy [22]. Specific PFMT exercises, called Kegels, are proven to be effective for female UI and pelvic organ prolapse and have been recommended as the initial therapeutic option [23], but the training needs proper instructions and close follow-up to be effective [24].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many articles published in 5 recent years [17,23,26,28,29,31] discussing the benefits of using FMS in the management of UI. Peng et al [34] state that "magnetic stimulation leads to an improvement in SUI without any reported safety concerns and an improvement in patient quality of life", but the authors agree on the uncertainty of the long-term effect of this technique.…”
Section: Introductionmentioning
confidence: 99%